Psychosocial impact of dental aesthetics, orthodontic treatment needs, and self-esteem in amazonian adolescents - Diego Carneiro; Arnoldo Brasil Muniz Junior; Caroline Nogueira de Moraes; Stéfany de Lima Gomes; Carmem do Nascimento Barros; Heloisa Cristina Valdrighi; Mario Vedovello Filho; Silvia Amélia Scudeler Vedovello (Bioscience Journal)
This study aimed to evaluate the psychosocial impact of dental aesthetics on the quality of life associated with normative and subjective orthodontic treatment needs and the self-esteem of adolescents living in the Brazilian Amazon region. It is a cross-sectional observational study conducted with 212 adolescents of both sexes enrolled in public schools in Boca do Acre (Amazonas, Brazil). The Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) assessed the psychosocial impact of malocclusion, and the Global Negative Self-Evaluation (GSE) scale evaluated the adolescents' self-esteem. The assessment of normative and subjective orthodontic treatment needs used the Index of Orthodontic Treatment Need (IOTN), including its dental health (DHC) and aesthetic (AC) components. Initial descriptive analyses of the data used absolute and relative frequencies, medians, and interquartile ranges. Poisson regression models with robust variance estimators appraised the prevalence ratios - with respective confidence intervals (95% CI) - of the associations with the PIDAQ. The prevalence of adolescents needing normative orthodontic treatment (IOTN-DHC) was 76.4%, and the subjective orthodontic treatment need prevalence (IOTN-AC) was 9.0%. Adolescents with low self-esteem reported a more significant impact on dental aesthetics (PR = 1.25; 95% CI: 1.14-1.36; p < 0.05). The study concluded that self-esteem and the psychosocial impact of dental aesthetics on the quality of life of Amazonian adolescents are significantly associated.